Red leaf symptoms in cotton its causes and management options - Praharaj, C S; Sankaranarayanan, K (Indian Farming, 2015)
The cause for the RLS disorder has been both biotic and abiotic factors. The reddening in leaves is attributed to magnesium deficiency, lower leaf N content, sudden fall in night temperature, low soil N supply, high temperature during the day coupled with low temperature at night, water stress and waterlogging. However, the biochemical studies proved that reddening of cotton leaves was related to an increased formation of anthocyanin pigments mainly cyanidin glycosides. Foliar application of urea @2%, DAP @2 % and MgSO4@1% at boll development period is helpful for managing leaf reddening symptoms in cotton. Further research is needed to provide a better understanding of factors that influence cotton diseases and to develop management strategies that reduce economic losses.